Girls' Series Fiction and American Popular Culture - D'Amico, LuElla (Lexington Books, 2016)
Girls' Series Fiction and American Popular Culture examines the ways in which young female heroines in American series fiction have undergone dramatic changes in the past 150 years, changes which have both reflected and modeled standards of behavior for America’s tweens and teen girls. Though series books are often derided for lacking in imagination and literary potency, that the majority of American girls have been exposed to girls’ series in some form, whether through books, television, or other media, suggests that this genre needs to be studied further and that the development of the heroines that girls read about have created an impact that is worthy of a fresh critical lens. Thus, this collection explores how series books have influenced and shaped popular American culture and, in doing so, girls’ everyday experiences from the mid nineteenth century until now. The collection interrogates the cultural work that is performed through the series genre, contemplating the messages these books relay about subjects including race, class, gender, education, family, romance, and friendship, and it examines the trajectory of girl fiction within such contexts as material culture, geopolitics, socioeconomics, and feminism.